Chlorogenic acid induces 4T1 breast cancer tumor's apoptosis via p53, Bax, Bcl‐2, and caspase‐3 signaling pathways in BALB/c mice. Issue 2 (15th October 2020) - Changizi, Zahra; Moslehi, Azam; Rohani, Ali Haeri; Eidi, Akram
Abstract: Despite all the new treatments, metastatic breast cancer (BC) causes many deaths. Chlorogenic acid (CGA) is a polyphenol compound with various pharmacological traits, such as anticancer properties. Targeting apoptotic death pathways has been propounded as the most effective therapeutic method in various cancers. In the current study, apoptotic agents such as p53, Bax, Bcl‐2, and caspase‐3 have been investigated. The experimental groups included saline, BC, CGA, protective (PR), and treatment (TM) groups. First, 4T1 mouse BC was established and then the effects of treatment with CGA were investigated through measurement of tumor weight and volume, metastatic nodules, liver biochemical tests, hematoxylin and eosin (H&E), immunohistochemistry (IHC) staining, and real‐time reverse transcription‐polymerase chain reaction (RT‐PCR) in experimental groups. The findings showed that CGA reduced tumor weight and volume in the PR group ( P < .05) and in the TM group ( P < .001). Surprisingly, it eliminated the tumors in the TM group. Metastatic nodules in the PR and TM groups were significantly reduced as compared with the BC group ( P < .001). The evaluation by H&E staining showed cell apoptosis in both the PR and TM groups. The results of real‐time RT‐PCR showed that CGA therapy increased the expression ratio of Bax/Bcl‐2 ( P < .001 and P < .05, respectively) and the expression of p53 ( P < .001 and P < .05, respectively) and caspase‐3 genes ( P < .01) in the PR and TM groups. The IHC data regarding the Bax/Bcl‐2 ratio confirmed the other results ( P < .001). The findings demonstrate that CGA plays a significant role in the induction of apoptosis and the treatment of 4T1 BC tumors in BALB/c mice.